RECENT TREND OF CHANGE OF FERTILITY IN NEPAL - Raya, Hikmat Bahadur (Researcher: A Research Journal of Culture and Society, 2018)
Fertility is one of the most predominant demographic factors of population dynamics. This article tries to analyze the trend of fertility of Nepal comparing with Global trend and the trends of other SAARC countries. This paper follows the quantitative analysis. The entire scope of discussion in this study is based on secondary sources of data. The results show that both ASFR and TFR have been continuously decreasing since 1990s. The decreasing rate is seen more in between 1998-2005s. Now the TFR is 2.3, so Nepal is in nearer to the replacement level of fertility rate. The marriage in early age is not still reduced remarkably that's why the fertility rate of this age group is not decreased as comparison to other age groups in Nepal. In the beginning, the TFRs of all SAARC countries were more than that of world. But in between past sixty decades, the TFR of this region is remarkably reduced and now it is similar to the world's figure except the Pakistan's. The TFR of Pakistan is still high in comparison to its neighbors. Fertility decline in Nepal has been occurring for several decades to till now. The reduction of fertility is beneficial in many domains, as it opens up completely for new employment and educational prospects for young women. It also creates new manpower for job market which helps to boost the economic growth. But continuous declination of fertility rate below the replacement level is not a good scenario in demography because it causes the negative growth rate of population and increase the dependency ratio. Researcher: A Research Journal of Culture and Society Vol. 3, No. 3, January 2018, Page: 72-80